2011
DOI: 10.1515/crelle.2011.061
|View full text |Cite
|
Sign up to set email alerts
|

Nombres réels de complexité sous-linéaire : mesures d'irrationalité et de transcendance

Abstract: International audienc

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
40
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
8

Relationship

8
0

Authors

Journals

citations
Cited by 22 publications
(42 citation statements)
references
References 35 publications
2
40
0
Order By: Relevance
“…As observed in [1] (see also Section 8.5 of [17]), it follows from the results of [14] and [4] that, for any integer b ≥ 2 and for any quasi-Sturmian word s over {0, 1, . .…”
Section: Rational Approximation Of Quasi-sturmian Numbers and Applicamentioning
confidence: 52%
“…As observed in [1] (see also Section 8.5 of [17]), it follows from the results of [14] and [4] that, for any integer b ≥ 2 and for any quasi-Sturmian word s over {0, 1, . .…”
Section: Rational Approximation Of Quasi-sturmian Numbers and Applicamentioning
confidence: 52%
“…Recent developments have shown that the use of quantitative versions of the Schmidt Subspace Theorem allows us often to strengthen or to complement results established by means of the qualitative Schmidt Subspace Theorem; see for instance the survey [16]. In particular, by combining ideas from [6,7,8] with new arguments, we have obtained in [17] transcendence measures for transcendental real numbers whose sequence of partial quotients a is such that n → p(n, a)/n is bounded.…”
Section: Discussionmentioning
confidence: 99%
“…As shown in [4], this powerful criterion has many applications and yields among other things the transcendence of irrational real numbers whose expansion in some integer base can be generated by a finite automaton. The latter result was generalized in [8], where we gave transcendence measures for a large class of real numbers shown to be transcendental in [4]. The key ingredient for the proof is then the Quantitative Subspace Theorem [32].…”
Section: Introductionmentioning
confidence: 92%
“…If α has unbounded partial quotients, the key auxiliary ingredient is Proposition 11.1 of [8] Consequently, if α has unbounded partial quotients, then ξ is a U 2 -number.…”
Section: Proofs Of Theorems 221 and 222mentioning
confidence: 99%